Solid-state thermal analysis of air- cooled polymer electrolyte membrane fuel cells with predictive empirical profiling / Wan Ahmad Najmi Wan Mohamed - Wan Mohamed, Wan Ahmad Najmi (Institute of Graduate Studies, UiTM, 2012)
The operation of Polymer Electrolyte Membrane (PEM) fuel cells are thermally sensitive, requiring an effective thermal engineering to cope with the generated heat. Air cooling for closed cathode PEM fuel cells is limited to stacks under 1.5 kWe. Due to great demand for fuel cells of 3 kWe or less with minimal system sizing, an effortwas taken to academically investigate the effect and behavior of various cooling channel designs, relative to PEM fuel cell operation, as a method for complementing the commercial needs. A scaled-down development approach was identified where three stacks, three cells each, with different cooling channel designs were fabricated for thermal characterization. The main objective was to develop a mathematical procedure in converting the empirical data at low electrical loadings to predict the thermal behavior of the stacks at expanded size and load.